Nanogenerator-Based Self-Charging Energy Storage Devices - Zhao, Kun; Wang, Yuanhao; Han, Lu; Wang, Yongfei; Luo, Xudong; Zhang, Zhiqiang; Yang, Ya (Nano-Micro Letters, 2019)
One significant challenge for electronic devices is that the energy storage devices are unable to provide sufficient energy for continuous and long-time operation, leading to frequent recharging or inconvenient battery replacement. To satisfy the needs of next-generation electronic devices for sustainable working, conspicuous progress has been achieved regarding the development for nanogenerator-based self-charging energy storage devices. Herein, the development of the self-charging energy storage devices is summarized. Focus will be on preparation of nanomaterials for Li-ion batteries and supercapacitors, structural design of the nanogenerator-based self-charging energy storage devices, performance testing, and potential applications. Moreover, the challenges and perspectives regarding self-charging energy storage devices are also discussed. Highlights: 1 The progress of nanogenerator-based self-charging energy storage devices is summarized. 2 The fabrication technologies of nanomaterials, device designs, working principles, self-charging performances, and the potential application fields of self-charging storage devices are presented and discussed. 3 Some perspectives and problems that need to be solved are described.